Enhancing rare cancer care in developing countries through patient advocacy: insights from the Desmoid Tumor Brazilian Association - Philippos Apolinario Costa; Carolina Menezes; Bruna Bianca Lopes David; Georgia Garofalo; Livia Prudente Barbieri; Fernando Campos (Therapeutic Advances in Medical Oncology)
Introduction: Desmoid tumors are soft-tissue neoplasms that can have profound impacts on the lives of people living with such diseases. As they are rare tumors, patients often have difficulty finding teams specialized in sarcomas and support networks. In low- and middle-income countries, the challenges are exacerbated due to a need for established networks and medication access. Discussion: In this setting, patient advocacy groups are important in supporting affected people. To this end, the Desmoid Tumor Brazilian Association (DTBA) was established to help mitigate those challenges. This paper highlights the perspectives of patients with desmoid tumors living in Brazil, obtained in a nationwide survey, and discusses aspects related to access to specialists, medications, education, and awareness in Brazil. Conclusions: The most commonly reported challenges in Brazil are access to educational material and specialists. The DTA continues to strive to improve support for people living in Brazil through initiatives such as Scientific and Educational Meetings, improving awareness, fostering science, and working on methods to facilitate access to medication and specialists.